Improving Activity and Learning Outcomes of Sciences Using the “Peter Pan” Model in Elementary School Students - Prasetyarini, Try Ajeng; Aslamiah; Cinantya, Celia; Maimunah; Refia Refianti, Wahdah (Journal of General Education Science, 2023)
The backgrounds of this research are the low activity and learning outcomes in the science learning content of the fifth grade elementary school students. The solution used to overcome this problem is to use the "PETER PAN" learning model which is a combination of power point media, learning models, guided inquiry, and team game matches.The purpose of this research are to analyze the increase in activity and student learning outcomes by using the "PETER PAN" combination model. This research used Classroom Action Research (CAR), which was conducted in 4 meetings. The subjects of this study were the fifth grade students of SDN 2 Hikun, Tabalong, totaling 15 students. The types of data used are qualitative and quantitative data. Data collection techniques with observations on student activities, learning motivation questionnaires and evaluation tests of learning outcomes. The data analysis technique used is qualitative data analysis in tabular form and data interpretation in the form of category percentages. From the results of the study, it was found that there was an increase in student activity classically by 60% increased to 93% at 4th meeting. The classical completeness of student learning outcomes at the first meeting was 47% increased to 100% at the 4th meeting. So, it can be concluded that the "PETER PAN" learning model can increase activity and learning outcomes in science learning content for fifth grade elementary school students.